A new fuzzy optimal allocation of detuned passive filters based on a Nonhomogeneous Cuckoo Search Algorithm considering resonance constraint. (June 2019) - Ayoubi, Masoud; Hooshmand, Rahmat-Allah
Abstract: Passive filters are used as one of the effective solutions to mitigate harmonics and improve power quality in electrical networks. In this paper, a new fuzzy approach is proposed for the allocation of detuned passive filters based on a Nonhomogeneous Cuckoo Search Algorithm (NoCuSa). In this method, a resonance index is inserted in the problem formulation to avoid being in a resonance condition after the allocation of passive filters. In this regard, the candidate locations for the installation of passive filters are first selected based on a sensitivity analysis. Then, the values and tuning orders of the passive filters are optimized by using the proposed algorithm for single- and multi-load levels while applying fixed and switched passive filters. In the simulations, different scenarios for optimal allocation of passive filters are investigated and compared with optimal allocation of capacitors. Finally, the fuzzy problem model is implemented on an IEEE 69-bus network by NoCuSa and compared with different optimization algorithms. The results demonstrate an improvement in the final annual net benefit by applying NoCuSa in comparison with other algorithms. In addition, another comparison made between the proposed method and those implemented on IEEE 69-bus system shows the efficiency of the proposed method. Highlights: A new technique based on NoCuSa algorithm is applied for optimization of passive filters allocation. Applying a new fuzzy model for considering the objective function and resonance constraints. Considering a new resonance constraint using a resonance index to avoid the probability of resonance in the network. Designing fixed and switched passive filters for multi-load level simulations. Applying different scenarios for passive filters allocation and comparison the results with capacitor placement.